Unity 5 game development : gameplay - Lavieri, Edward D., Jr.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Get hands-on experience creating a game consisting of a user interface and an interactive level. Build your first functioning game with Unity 5. Grasp game development fundamentals in a practical way. Polish game objects."--Resource description page.
Title from resource description page (Safari, viewed May 22, 2017).
Presenter, Edward Lavieri.
Keywords: Unity (Electronic resource); Computer games -- Programming; Computer games -- Design; Electronic books